Emodin induces apoptosis and autophagy of fibroblasts obtained from patient with ankylosing spondylitis - Ma C; Wen B; Zhang Q; Shao P; Gu W; Qu K; Shi Y; Wang B (Dove Medical Press, 2019)
Cong Ma, Bo Wen, Qin Zhang, Pei-Pei Shao, Wen Gu, Kun Qu, Yang Shi, Bei Wang Department of Rheumatology and Immunology, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, Beijing 100010, People’s Republic of China Background: Ankylosing spondylitis (AS) is a type of rheumatoid disease, which has been reported to be associated with the excessive proliferation of fibroblasts recently. Emodin, a single component from a traditional Chinese medicine Rheum palmatum, exerts anti-inflammation and antirheumatic arthritis activities. However, could emodin be used to treat AS remains unclear? Thus, this study aimed to investigate the effect of emodin on AS.Methods: Fibroblasts obtained from patients with AS were used in the current study. In addition, multiple cellular and molecular biology techniques such as Cell Counting Kit-8, Western blotting, flow cytometry, monodansylcadaverine staining, and immunofluorescence assay were applied as well.Results: Emodin-induced apoptosis of fibroblasts obtained from patient with AS via increasing active caspase-9, active caspase-3, and Bax levels and downregulating Bcl-2. Meanwhile, emodin enhanced autophagy in fibroblasts via upregulation of the expression of Atg12, Atg5, and Beclin 1, which was further confirmed by monodansylcadaverine staining. As expected, autophagy inhibitor 3-methyladenine (3MA) completely reversed emodin-induced autophagy in fibroblasts. Moreover, 3MA significantly increased emodin-induced apoptosis of fibroblasts obtained from patient with AS by increasing the levels of γH2AX, active caspase-9, active caspase-3, and cleaved poly ADP-ribose polymerase.Conclusion: Our results indicated that emodin effectively induced apoptosis and autophagy of fibroblasts obtained from patient with AS. In addition, suppression of autophagy enhanced emodin-induced apoptosis in fibroblasts. Therefore, we proposed that combination of emodin with autophagy inhibitor might be a potent strategy for improving the symptoms of AS in the future. Keywords: emodin, apoptosis, autophagy, 3MA, ankylosing spondylitis